The Effect of Using YouTube Video on Students’ Ability of Senior High School in Writing Analytical Exposition Texts - Mutiara Savira Kurnia; Syofia Delfi Delfi; Mahsyur Mahsyur (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aimed to know about the effect of using YouTube video of 11th grade students of SMAN 1 Kampung Dalam Kabupaten Padang Pariaman in writing analytical exposition text. The sample of this research was taken by using the quota sampling technique. The number of the students was 20 students. The data was collected by using pretest and posttest. This research used four types of aspects in writing, namely content, organization, language use, and vocabulary. The result showed students have the higher total average after using YouTube video in writing analytical exposition text. It seems using YouTube video can make students developing their ability in writing.